BLUE LIGHT FOR THE TREATMENT OF ACNE VULGARIS - Farias, Thayssa Gomes; da Silva, Marcelle Abreu; Ferreira, Ana Caroline da Silva; de Paoli, Flávia; da Fonseca, Adenilson de Souza (Seven Editora, 2026)
Acne vulgaris represents a persistent global dermatological challenge due to the increasing resistance of Cutibacterium acnes strains to conventional antibiotics. In this context, blue light phototherapy emerges as a sophisticated non-pharmacological intervention, based on the selective photoexcitation of endogenous bacterial porphyrins, coproporphyrin III and protoporphyrin IX. Maximum absorption in the Soret band triggers a type II photochemical reaction, resulting in the production of singlet oxygen and reactive oxygen species that promote targeted bactericidal effects and the modulation of pro-inflammatory cytokines. In addition to its established clinical efficacy for inflammatory lesions (papules and pustules), blue light therapy has a high safety profile, often enhanced by synergistic association with red light to stimulate tissue repair and reduce sebaceous gland activity. Technological advancements, observed in the transition from clinical systems to accessible home devices, solidify this modality as a viable alternative in the treatment of acne vulgaris, either alone or in conjunction with conventional treatments.